Leadership Should or Should Not Delegate Communication? (A Systematic Literature review: The Art of Delegation) - Gibriel Badjie (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2020)
Communication and delegation are two important and parts of the leadership function. However, it is still a matter of debate whether leaders can delegate responsibility for communication, especially policy information, to those under their authority. Various opinions state that there is no prohibition for leaders to delegate their responsibilities because this is the leader's prerogative. This study aims to identify whether leadership should or should not delegate communication. The method used in this study was Systematic Literature Review (SLR). The SLR method is used to identify, review, evaluate, and interpret all available research by topic area phenomenon of interest, with specific relevant research questions. The results showed that leaders can delegate communication but it is highly dependent on the type, style, and approach of leadership on the table at that time. Such a leadership style or approach will automatically influence the style and approach of communication and delegation.